Post Ablative Hypothyroidism in Hyperthyroid Patients: Single Institute Based Observational Study - Yasmin, Farida; Naznin, Afroza; Sharmin, Samira; Rahman, Hosne Ara (Bangladesh Journal of Nuclear Medicine, 2024)
Objective: To determine the incidence of hypothyroidism after radioactive iodine (131I) ablation of hyperthyroid patients attending the thyroid division of Institute of Nuclear Medicine & Allied Sciences (INMAS), Mitford. Method: This retrospective observational study was conducted among hyperthyroid patients of INMAS, Mitford, who received radioiodine therapy between the period of 2019 to 2023. A total of 63 subjects of both sexes were included in this study. Patients who received a second dose of radioiodine as therapy and lost to follow-up were excluded. Patient data were collected from the medical records. Result: The incidence of post-ablative hypothyroidism within six months was 55.45%. Among them, 1.59% became hypothyroid at one month, and 26.98% became hypothyroid at three and six months respectively. Conclusion: This study showed a high incidence of hypothyroidism within six months of radio-iodine therapy (RAI therapy). Bangladesh J. Nuclear Med. 26(2): 151-154, 2023